"It's a Jihad": Justifying Violence towards the Ahmadiyya in Indonesia. Issue 1 (May 2021) - Burhani, Ahmad Najib
Abstract: The concept of al-wala' wa-l-bara' (loyalty and disavowal) has become the ideology of modern Salafism; it is used to justify unfriendly relationships with non-Muslims. This concept is usually implemented by reserving love only for fellow Muslims and showing insularity towards non-Muslims. What is the ideological concept that guides some Muslims in their relationship with groups that are considered heretics? This article intends to scrutinize the theological matrix used by vigilante groups in their anti-heresy campaign or attacks on the Ahmadiyya. It also aims to determine why some people believe that persecuting the Ahmadiyya is a theologically justifiable idea. What theological and ideological reasons can be used to justify attacks against the Ahmadiyya community? How do they cope with the conflict between divine law and human/state law? This article argues that instead of feeling guilty, the perpetrators of faith-based violence often feel they have just fulfilled a good religious duty. Committing violence against religious groups deemed heretics is believed to be more than al-amr bi al-màrūf wa al-nahy `an al-munkar ("commanding right and forbidding wrong")—it is a jihad. Violence is seen not as an illegal act, but as a "virtue" or an effort to save them from the punishment of God in Hell. In justifying the breaching of state law, the idea of a hierarchy in the law is constructed, i.e. state/human law is hierarchically lower than divine law, so attacking the Ahmadiyya is seen as a transgression of human law for the sake of upholding the divine view.